White Matter Changes Along the Electrode Lead in Patients Treated With Deep Brain Stimulation - Erasmi, Richard; Granert, Oliver; Zorenkov, Dmitry; Falk, Daniela; Wodarg, Fritz; Deuschl, Günther; Witt, Karsten (Frontiers in Neurology, 2018)
Introduction: Deep brain stimulation (DBS) is an established treatment for various movement disorders. There is little data available about the potential damage to brain parenchyma through DBS treatment. The objective of this study was to investigate the occurrence of signal changes on magnetic resonance imaging (MRI) in patients treated with DBS. Methods: We retrospectively analyzed MRI scans of 30 DBS patients (21 patients with Parkinson’s disease, 3 patients with dystonia and 6 patients with tremor) that had undergone additional MRI scans after DBS surgery (ranging from 2 months to 8 years). Axial T2 sequences were analyzed by two raters using a standardized lesion mapping procedure. Results: 26 out of 30 analyzed patients showed hyperintense white matter changes surrounding the DBS lead (mean volume = 2.43 ml). Lesions were prominent along the upper half of the electrode lead within the subcortical white matter with no abnormalities along the lower lead. Their volume was significantly correlated to the time from surgery to MRI and to the number of microelectrodes used in surgery, but was independent from underlying disease (Parkinson’s disease, dystonia, tremor), target structure (STN, GPi, VIM), demographical data or cardiovascular risk factors. Discussion: White matter changes along the electrode leads in DBS patients are a frequent finding. These changes seem to evolve with certain latency after surgery and might be radiologically classified as a gliosis. Our findings identifies the number of intraoperatively used microelectrodes as a risk factor in the formation of gliosis. Therefore, mechanical damage at the time of surgery and an individuell tissue response might contribute to their evolution. Further studies are needed to define the exact mechanisms and their clinical impact.